2020
DOI: 10.1155/2020/8838535
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Method for Assessing Meat Freshness Using Fusing Electronic Nose, Computer Vision, and Artificial Tactile Technologies

Abstract: The traditional methods cannot be used to meet the requirements of rapid and objective detection of meat freshness. Electronic nose (E-Nose), computer vision (CV), and artificial tactile (AT) sensory technologies can be used to mimic humans’ compressive sensory functions of smell, look, and touch when making judgement of meat quality (freshness). Though individual E-Nose, CV, and AT sensory technologies have been used to detect the meat freshness, the detection results vary and are not reliable. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In recent years, the electronic nose system developed in the laboratory has been widely used in the agricultural field ( 17 , 18 ). Based on these studies, the respiratory sample collection system in this paper was developed for diabetes detection, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the electronic nose system developed in the laboratory has been widely used in the agricultural field ( 17 , 18 ). Based on these studies, the respiratory sample collection system in this paper was developed for diabetes detection, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Studies conducted on apples showed great variation in sourness, saltiness, and umami with the significant amount of esters and the presence of volatile compounds like hexyl butyrate and toluene (Zhu et al 2020 ). Similar studies were evaluated to analyze the meat freshness (Weng et al 2020 ). It is noteworthy to mention the most recent advancement of 3D printed chip technology.…”
Section: Application Of Lab-on-a-chip Devices In the Food Industrymentioning
confidence: 99%
“…This transform means that Hx can be used as an important indicator to reveal the freshness of sh since its accumulation is proportional to the storage time. Currently, to meet the freshness Weng, et al, 2020) and gas chromatography-mass spectrometry (GC-MS) technology(P. Li, Geng, Li, & Niu, 2020) have been already been applied to realize the measuring of Hx. Although these methods are highly repetitive, accurate, and reliable, the request of expensive equipment, professional personnel, and specialized laboratory limit their wide application.…”
Section: Introductionmentioning
confidence: 99%